Evaluating different scenarios for Tradable Green Certificates by game theory approaches - Meysam Ghaffari; Ashkan Hafezalkotob (Journal of Industrial Engineering International, 2019)
Right now employment of polices and tools to decrease the carbon emission through electricity generation from renewable resources is one of the most important problem in energy policy. Tradable Green Certificate (TGC) is an economics mechanism to support green power generation. Any country has the challenge to choose an appropriate policy and mechanism for design and implementation of TGC. The purpose of this study is to help policy makers to design and choose the best scenario of TGC by evaluating six scenarios, based on game theory approach. This study will be useful for increasing the effectiveness of TGC system in interaction with electricity market. Particularly, the competition between thermal and renewable power plants is modeled by mathematical modeling tools such as cooperative games like Nash and Stackelberg. Each game is modeled by taking into account of the two following policies. The results of the six scenarios and the sensitivity analysis of some key parameters have been evaluated by numerical studies. Finally, in order to evaluate the scenarios we calculated the level of social welfare in the all scenarios. The results of all models demonstrate that when the green electricity share (minimum requirement) increases the TGC price decreases. Moreover, in all scenarios when the minimum requirement is 100% then the maximum level of social welfare is not met. Also when the minimum requirement is less than 50%, the scenarios with the market TGC price policy have more social welfare in comparison with the scenarios with fixed TGC price policy.
Keywords: 650; Green electricity; Tradable Green Certificate; Game theory; Mathematical modeling